2005
DOI: 10.1051/0004-6361:20041941
|View full text |Cite
|
Sign up to set email alerts
|

X-ray properties of active M dwarfs as observed by XMM-Newton

Abstract: Abstract. We present a comparative study of X-ray emission from a sample of active M dwarfs with spectral types M3.5-M4.5 using XMM-Newton observations of two single stars, AD Leonis and EV Lacertae, and two unresolved binary systems, AT Microscopii and EQ Pegasi. The light curves reveal frequent flaring during all four observations. We perform a uniform spectral analysis and determine plasma temperatures, abundances and emission measures in different states of activity. Applying multi-temperature models with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
87
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 40 publications
(63 reference statements)
19
87
1
Order By: Relevance
“…Early results of the XMM-Newton monitoring program of the α Cen stars were presented by Robrade & Schmitt (2005). Most strikingly an X-ray dimming of α Cen A by an order of magnitude within three years was observed in the bandpass of the EPIC detectors, caused by a strong decrease in emission measure at a few MK.…”
Section: α Centaurimentioning
confidence: 99%
See 1 more Smart Citation
“…Early results of the XMM-Newton monitoring program of the α Cen stars were presented by Robrade & Schmitt (2005). Most strikingly an X-ray dimming of α Cen A by an order of magnitude within three years was observed in the bandpass of the EPIC detectors, caused by a strong decrease in emission measure at a few MK.…”
Section: α Centaurimentioning
confidence: 99%
“…A flare of similar energy from α Cen B which was detected in 01/2004 at about activity maximum was discussed in Robrade & Schmitt (2005); likely these events are among the faintest stellar flares with a clearly observed rise and decay phase detected in X-rays. Several small and intermediate events are also detected from 61 Cyg A and 61 Cyg B.…”
Section: Flaresmentioning
confidence: 99%
“…Fe xiii is an indicator for cool coronal plasma (≈1.5 MK), while typical coronal emission measure distributions of earlier M dwarfs peak around 7-8 MK (e.g. Robrade & Schmitt 2005), i.e., temperatures where the ionization equilibrium is shifted towards Fe xvii. Fuhrmeister et al (2007) found significant amounts of cooler plasma in the corona of CN Leo from X-ray spectra obtained with XMM-Newton, consistent with the Fe xiii line fluxes from simultaneous optical spectroscopy.…”
Section: The Active M Dwarf Cn Leomentioning
confidence: 99%
“…This value increases to 1.1 × 10 30 erg s −1 during the flare. The quiescence luminosity is very similar to the typical L X of other dMe stars (Mitra-Kraev et al 2005;Robrade & Schmitt 2005), and is lower than for PMS T Tauri stars or RS CVn interacting binaries. Moreover, the log(L X /L BOL ) ratio amounts to −3.3 in quiescence and −2.6 during the flare, which is the typical ratio observed at the saturation limit for coronally-active sources (Riaz et al 2006).…”
Section: Rxs J1715024−333344mentioning
confidence: 61%
“…First, the flare, since magnetically active M dwarves frequently present flares in their X-ray emission (e.g. Raassen et al 2003;Robrade & Schmitt 2005;Wargelin et al 2008). The hardening during the flare (associated with a higher emission measure of the hottest components) and the shifted maximum of the hard X-ray lightcurve are also indicative of a coronal source (Wargelin et al 2008).…”
Section: Rxs J1715024−333344mentioning
confidence: 99%